2020
DOI: 10.1016/j.celrep.2020.108263
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics of Parkinson’s Disease Human In Vitro Models Reveals Dopamine Neuron-Specific Stress Responses

Abstract: Highlights d Deconvolution of in vitro human dopamine neuron heterogeneity by scRNA-seq d Identification of dopamine subtypes with transcriptionally distinct profiles d Cell type-specific gene perturbations of cholesterol metabolism in stress response d PD GWAS associated gene expression analysis at the singlecell level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 64 publications
1
97
0
Order By: Relevance
“…We harvested more than 10,000 hKO1-positive cells from a single brain, which are su cient for most downstream analyses such as RNA-seq, bisul te sequencing, and ChIP-sequencing. Single-cell RNA-seq (scRNA-seq) has recently been used to obtain transcriptome pro ling of small cell populations, including neurons 23,24,26,39 . Although scRNA-seq provides a great platform for pro ling individual cells, technical issues such as high noise, low capture e ciency, and substantial cost remain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We harvested more than 10,000 hKO1-positive cells from a single brain, which are su cient for most downstream analyses such as RNA-seq, bisul te sequencing, and ChIP-sequencing. Single-cell RNA-seq (scRNA-seq) has recently been used to obtain transcriptome pro ling of small cell populations, including neurons 23,24,26,39 . Although scRNA-seq provides a great platform for pro ling individual cells, technical issues such as high noise, low capture e ciency, and substantial cost remain.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the PD model study, our reporter mice and neuron isolation protocol also offer other applications. For instance, it can be applied in the analysis of DA neuron subtypes, which show distinct expression patterns in marker genes 23,26,30,39 . Although scRNA-seq and immunohistochemical analyses demonstrate the heterogeneity of DA subpopulations in the brain, their speci c function is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hubs, or highly connected neurons, are a common feature of complex networks 42,43,[47][48][49] , but dopaminergic networks have yet to be tested empirically for the existence of hub neurons. Consistently, many investigations describe the substantia nigra pars compacta dopaminergic network as more vulnerable than the adjacent ventral tegmental area, albeit with a less understood mechanism 30,[50][51][52][53][54][55][56][57] . While the origin of these regional differences has remained nebulous, network analysis can provide clues to how functional network organization of these regions may contribute to resilience or failure within the network that ultimately lead to neurocognitive and behavioral dysfunction.…”
Section: Introductionmentioning
confidence: 95%
“…Approaches that nominate enrichment in specific cell types have been useful in identifying likely genes as most tissues have heterogeneous cellular composition. Several approaches have nominated dopamine neurons (4)(5)(6)(7), which are principal cell types lost in PD, as mediators of neurodegeneration, although other studies have identified non-neuronal cells including oligodendrocytes and oligodendrocyte precursor cells (4,8) as contributing to disease risk. Such approaches rely on the presumed mechanism that non-coding variants affect gene expression, which can be inferred by mapping expression quantitative trait loci (eQTL).…”
Section: Introductionmentioning
confidence: 99%